Response to Long-term Vitamin D Therapy for Bone Disease in Children With Sickle Cell Disease. Issue 6 (August 2018) - Williams, Kristen M.; Lee, Margaret T.; Licursi, Maureen; Brittenham, Gary M.; Fennoy, Ilene
Abstract : Patients with sickle cell disease (SCD) are at risk for bone fragility from multiple factors including vitamin D deficiency. To date, no studies have evaluated the efficacy and safety of long-term vitamin D therapy for bone disease in children with SCD. We report a cohort of 4 children with SCD found to have severe vitamin D deficiency, secondary hyperparathyroidism, and abnormal bone mineral density treated with monthly high-dose oral cholecalciferol over 2 years. All patients exhibited a positive response to therapy without hypervitaminosis D or hypercalcemia. Further studies are needed to standardize guidelines for optimal vitamin D dosing and prevention of toxicity.